High-performance composite electric heating film and preparation process thereof

Through the preparation of modified base film and three-dimensional composite electro-heating material, the problem of insufficient performance of the electro-heating film is solved, the conductive thermal performance and heating efficiency are improved, energy loss is reduced, and local overheating is prevented.

CN119300189AInactive Publication Date: 2025-01-10SHENZHEN DELONG ELECTRICAL APPLIANCE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411828799.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There is room for improvement in the performance of the existing electrical heating films, especially the problems of low heating efficiency, uneven heating distribution, poor stability and large energy losses, and poor compatibility between carbon fiber and matrix resin leads to local overheating.

Method used

By preparing modified base films, conductive base films and three-dimensional composite electrothermal heating materials, a high-temperature stable structure is formed by cross-linking of glucosaccharides and acetic bacterial cellulose with polyether sulfone, and a three-dimensional network of carbon nanotubes and carbon fibers is generated by chemical vapor deposition method. and surface modification to improve compatibility and dispersion.

Benefits of technology

The high temperature resistance and flexibility of the modified base film are significantly improved, the conductive thermal performance of the composite electric heating film is enhanced, energy loss is reduced, and local overheating is prevented, achieving a more uniform heating efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a high-performance composite electric heating film and a preparation process thereof, and belongs to the technical field of heating materials. The preparation process comprises the following steps: preparing the modified base membrane; preparing a modified conductive base film; preparing a three-dimensional composite electric heating material; a surface-modified three-dimensional composite electric heating material; and preparing the composite electric heating film. The preparation method comprises the following steps: activating gluconacetobacter aceti, culturing in a culture medium, producing a bacterial cellulose membrane, purifying, drying, adding into a dimethyl sulfoxide solution of polyethersulfone, adding a cross-linking agent benzoyl peroxide, carrying out cross-linking polymerization on polyethersulfone and bacterial cellulose, and modifying polyethersulfone to obtain the bacterial cellulose modified polyethersulfone. According to the preparation method, the high-temperature resistance of the prepared modified base membrane can be effectively improved, the toughness of polyether sulfone can be improved, and the prepared modified base membrane has relatively good flexibility and is suitable for more use scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heating materials, and in particular to a high-performance composite electric heating film and a preparation process thereof. Background Art

[0002] In modern industry and daily life, people have higher and higher requirements for the performance of electric heating films. For example, in the fields of heating and keeping warm in electronic equipment, building heating, medical care, etc., electric heating films are required to have higher heating efficiency, more uniform heat distribution, better stability and reliability. In addition, with the increasing awareness of environmental protection, the demand for low-energy consumption and pollution-free electric heating films is also becoming increasingly urgent.

[0003] Although the electric heating films currently available on the market have met some of the needs to a certain extent, there is still a lot of room for improvement in terms of performance. In the prior art, electric heating materials are usually added to the matrix resin to form an electric heating slurry, which is coated on a resin film or glass fiber cloth, and then cured and connected to the electrode to form an electric heating film substrate. Finally, an insulating layer is composited on both sides of the base sheet to form an electric heating film. However, electric heating materials including carbon fiber, graphene, carbon nanotubes, etc. have poor compatibility with the matrix resin and are prone to agglomeration, resulting in poor dispersion in the matrix resin, which can easily lead to local overheating of the electric heating film, causing safety hazards. Moreover, since the matrix resin is insulating, it is easy to cause the resistance of the electric heating film to be too large, resulting in lower heating efficiency and greater energy loss.

[0004] Therefore, it is necessary to develop a high-performance composite electric heating film and its preparation process that generates heat evenly and saves energy, so as to meet the heating needs of different fields and promote the further development of electric heating technology. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-performance composite electric heating film and a preparation process thereof.

[0006] A preparation process of a high-performance composite electric heating film comprises the following steps: S1: Preparation of modified base film The activated Gluconacetobacter was inoculated and cultured to prepare a bacterial cellulose membrane, which was purified and sliced, added into a polyethersulfone solution, and then benzoyl peroxide was added for reaction, and then the modified base membrane was obtained by scraping and vacuum drying. S2: Preparation of modified conductive base film Pyrrole is added to deionized water in a volume ratio of 1: (140-150), stirred and mixed evenly, and then anthraquinone-2-sulfonic acid sodium salt is added, ultrasonic treatment is performed for 20-30 minutes, and uniform dispersion is obtained to obtain a mixed solution, and then the modified base film is immersed in the mixed solution, and allowed to stand in a 0°C ice water bath for 1-2 hours, and then ferric chloride is added, and after standing for reaction for 2-3 hours, the modified base film after the reaction is taken out, and washed and dried to obtain a modified conductive base film; S3: Preparation of three-dimensional composite electric heating materials The growth raw materials are prepared with nickel nitrate hexahydrate, cobalt nitrate hexahydrate, aluminum nitrate nonahydrate and urea as raw materials, and then placed in a tube furnace, and methane and argon are introduced to react, and then immersed in deionized water, and diluted hydrochloric acid is added and high-pressure sealing reaction is carried out to obtain a three-dimensional composite electric heating material; S4: Surface modified three-dimensional composite electric heating material The three-dimensional composite electric heating material is dispersed in toluene, and (3-aminopropyl) triethoxysilane is added to react, then dispersed in dichloromethane together with pyridine, and succinic anhydride is added to react, and finally dispersed in a cholesterol dimethyl sulfoxide solution, and concentrated sulfuric acid is added to react to obtain a surface-modified three-dimensional composite electric heating material; S5: Preparation of composite electric heating film Xylene, 2,4-diphenylmethane diisocyanate, castor oil and dibenzoyl peroxide solution are mixed to prepare polyurethane resin, and then epoxy-modified silicone resin, polysiloxane silicone resin, xylene and dibutyltin dilaurate are added to prepare modified polyurethane adhesive solution, and then the above-mentioned modified three-dimensional composite electric heating material is added to prepare electric heating adhesive solution, and the above-mentioned modified conductive base film is immersed in the electric heating adhesive solution to prepare a composite heating film material, and then electrodes are prepared on the surface of the composite heating film material and packaged to obtain a composite electric heating film.

[0007] Furthermore, S1 specifically includes the following steps: S1.1: Activate Gluconacetobacter and inoculate into the culture medium, culture at 28-32°C for 6-8 days, collect the membrane material produced on the surface of the culture medium, and repeatedly rinse with deionized water for 3-5 times to obtain the bacterial cellulose membrane; S1.2: soaking the bacterial cellulose film in a 0.1 mol / L sodium hydroxide solution, and heating it at 90-100°C for 1-2 hours, and then soaking it in deionized water for 1-2 hours, taking it out and draining it, pouring it with liquid nitrogen, and performing vacuum freeze drying, and then slicing it to obtain bacterial cellulose; S1.3: Add polyethersulfone to dimethyl sulfoxide at a solid-liquid ratio of 1 g: (35-45) mL, stir thoroughly to dissolve, and obtain a polyethersulfone solution; S1.4: adding the bacterial cellulose to the polyethersulfone solution, stirring and mixing, and then adding benzoyl peroxide while stirring to obtain a mixed reaction solution; S1.5: Transfer the mixed reaction solution to a constant temperature water bath, heat and stir at 60-80°C for 2-4 hours, and then keep it at this temperature for 8-10 hours to obtain a casting solution; S1.6: Use a scraper to apply the above casting solution on a glass plate, and place it in a vacuum drying oven for vacuum drying for 10-12 hours to obtain a modified base film.

[0008] Furthermore, S3 specifically includes the following steps: S3.1: Add nickel nitrate hexahydrate, cobalt nitrate hexahydrate, aluminum nitrate nonahydrate and urea into deionized water at a solid-liquid ratio of 1 g: (1.2-1.6) g: (1.1-1.3) g: (120-130) g: (100-120) mL, heat and stir at 70-80 ° C for 8-10 h, and stand for 10-12 h, then filter and wash, and then calcine at 800-900 ° C for 1-2 h to obtain a growth raw material; S3.2: The above growth raw materials are evenly dispersed on the substrate, and then placed in a tube furnace, with methane as the carbon source and argon as the protective gas, the methane flow rate is controlled to be 30-40sccm, and the argon flow rate is controlled to be 45-55sccm, the tube furnace is heated to 800-1000°C at 5°C / min, and after the reaction is kept at this temperature for 20-30min, the temperature is lowered to 40-50°C at 5°C / min, and then cooled to room temperature along with the furnace to obtain a composite material; S3.3: Place the above composite material in a high-pressure reactor, add 0.1 mol / L hydrochloric acid aqueous solution until the composite material is completely immersed, stir and mix evenly, and react at 180-200°C under high pressure and sealed for 10-12 hours. After naturally cooling to room temperature, filter, wash and dry to obtain a three-dimensional composite electric heating material.

[0009] Furthermore, S4 specifically includes the following steps: S4.1: Add the three-dimensional composite electric heating material prepared in step S3.3 to toluene at a solid-liquid ratio of 1 g: (35-45) mL, ultrasonically disperse for 20-30 min, then add (3-aminopropyl) triethoxysilane, stir and mix thoroughly to obtain a mixed suspension; S4.2: heating the mixed suspension at 110-120° C. for reflux reaction for 12-16 hours, cooling naturally to room temperature, centrifuging, washing and drying to obtain an amino-functionalized composite material; S4.3: Add the amino-functionalized composite material and pyridine into dichloromethane at a solid-liquid ratio of 1 g: (8-10) mL: (10-12) mL, ultrasonically disperse for 20-30 min, then add succinic anhydride, stir and react for 16-18 h, centrifuge, wash and dry to obtain a carboxyl-functionalized composite material; S4.4: Cholesterol is dissolved in dimethyl sulfoxide at a solid-liquid ratio of 1 g: (30-40) mL, and then the carboxyl functionalized composite material is added at a solid-liquid ratio of 1 g: (60-70) mL, and ultrasonically dispersed for 20-30 min to obtain a composite suspension; S4.5: Add concentrated sulfuric acid to the composite material suspension in a volume ratio of 1: (100-110), and heat under reduced pressure at 60-70°C for 8-10 hours. After naturally cooling to room temperature, centrifuge, wash and vacuum dry to obtain a surface-modified three-dimensional composite electric heating material.

[0010] Furthermore, S5 specifically includes the following steps: S5.1: By weight, 5-10 parts of xylene and 40-50 parts of 2,4-diphenylmethane diisocyanate are thoroughly stirred and mixed, and then 40-50 parts of castor oil are added, and heated and stirred at 70-80° C. for 2-3 hours, and then 1-2 parts of dibenzoyl peroxide and dichloromethane are added, and stirring is continued for 1-2 hours, and degassing is carried out under reduced pressure to obtain a polyurethane resin; S5.2: Add epoxy-modified silicone resin, polysiloxane silicone resin, xylene and dibutyltin dilaurate to the above polyurethane resin in a mass ratio of (10-12): (0.5-1): (0.5-1): (2-3): 1, stir and disperse evenly to obtain a modified polyurethane glue solution; S5.3: adding the surface-modified three-dimensional composite electric heating material obtained in step S4.5 to the modified polyurethane adhesive solution according to a mass ratio (1.1-1.3): 1, stirring and mixing evenly, and obtaining the electric heating adhesive solution after vacuum degassing; S5.4: Immerse the modified conductive base film obtained in step S2 in the above-mentioned electric heating glue solution, ultrasonically treat for 10-20 minutes, then take out and dry and solidify to obtain a composite heating film material; S5.5: Prepare electrodes on both sides of the surface of the composite heating film material, respectively, and then package them to obtain a composite electric heating film.

[0011] Further, the culture medium includes 20 g / L glucose, 10 g / L yeast extract, 5 g / L peptone, 6 g / L disodium hydrogen phosphate dodecahydrate, 1.5 g / L citric acid monohydrate and 0.5 g / L magnesium sulfate heptahydrate.

[0012] Furthermore, the molar ratio of polyethersulfone to bacterial cellulose is 1:(0.6-0.8), and the solid-liquid ratio of benzoyl peroxide to polyethersulfone solution is 1 g:(80-100) mL.

[0013] Furthermore, the molar ratio of anthraquinone-2-sulfonic acid sodium salt to pyrrole is 1:(8-10), and the molar ratio of ferric chloride to pyrrole is (1.3-1.5):1.

[0014] Furthermore, the volume ratio of (3-aminopropyl)triethoxysilane to toluene is 1:(140-150), and the mass ratio of succinic anhydride to the amino-functionalized composite material is (2-3):1.

[0015] A high-performance composite electric heating film is prepared by any of the above-mentioned preparation processes for a high-performance composite electric heating film.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention activates Gluconacetobacter and cultured it in a culture medium to produce a bacterial cellulose membrane. After purification and drying, the membrane is added to a dimethyl sulfoxide solution of polyethersulfone, and then a cross-linking agent benzoyl peroxide is added to cross-link and polymerize the polyethersulfone and the bacterial cellulose to modify the polyethersulfone. Since the bacterial cellulose has a high degree of crystallinity and can maintain a stable structure at high temperatures, after the polyethersulfone is modified by bacterial cellulose, the high temperature resistance of the obtained modified base membrane can be effectively improved. In addition, since the polyethersulfone and the bacterial cellulose are cross-linked and polymerized to form a three-dimensional network structure, the intermolecular interaction is enhanced and the stress transfer is improved, which is beneficial to improve the toughness of the polyethersulfone, so that the obtained modified base membrane has good flexibility and is suitable for more usage scenarios.

[0017] 2. The present invention first utilizes nickel nitrate hexahydrate, cobalt nitrate hexahydrate, aluminum nitrate nonahydrate and urea to mix and heat to react to generate a ternary metal hydroxide, which is then calcined at high temperature to form a growth raw material, and then uses methane as a carbon source and the growth raw material as a catalyst to generate carbon nanotubes and carbon fibers in situ by chemical vapor deposition. After removing the growth raw material through a high-pressure hydrothermal reaction, a three-dimensional composite electric heating material in which carbon nanotubes and carbon fibers are combined to form a three-dimensional network structure is obtained. By forming a three-dimensional network structure, the carbon nanotubes and carbon fibers can complement each other at different scales to form more conductive and thermal conductive paths, thereby reducing energy loss during transmission. Therefore, compared with adding a single carbon nanotube or a single fiber to the electric heating glue, adding a three-dimensional composite electric heating material can effectively improve the conductive and thermal conductive properties of the composite heating film formed by the electric heating glue, thereby improving the heating efficiency of the composite electric heating film and reducing energy loss.

[0018] 3. The present invention first uses (3-aminopropyl) triethoxysilane to perform surface modification on the three-dimensional composite electric heating material to functionalize its surface with amino groups, then uses succinic anhydride to perform surface modification on the three-dimensional composite electric heating material with amino groups to functionalize its surface with carboxyl groups, and finally uses cholesterol to perform surface esterification modification on the three-dimensional composite electric heating material with carboxyl groups to graft cholesterol onto the surface of the three-dimensional composite electric heating material. Since the hydrophobic part of cholesterol can be better compatible with the organic chain segment of polyurethane, the compatibility of the three-dimensional composite electric heating material with modified polyurethane glue can be improved, so as to improve its dispersibility in the modified polyurethane glue and prevent the prepared composite electric heating film from having local overheating problems. DETAILED DESCRIPTION

[0019] The following is a detailed description of a high-performance composite electric heating film and its preparation process provided by the present invention in conjunction with specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies.

[0020] Example 1 A preparation process of a high-performance composite electric heating film comprises the following steps: S1: Preparation of modified base film S1.1: Activate Gluconacetobacter and inoculate it into a culture medium, and after static culture at 28°C for 6 days, collect the film material produced on the surface of the culture medium, and repeatedly rinse it with deionized water for 3 times to obtain a bacterial cellulose film, wherein the culture medium includes 20 g / L glucose, 10 g / L yeast extract, 5 g / L peptone, 6 g / L disodium hydrogen phosphate dodecahydrate, 1.5 g / L citric acid monohydrate and 0.5 g / L magnesium sulfate heptahydrate; S1.2: soak the bacterial cellulose film in a 0.1 mol / L sodium hydroxide solution and heat it at 90°C for 1 hour, then soak it in deionized water for 1 hour, take it out and drain it, then pour it with liquid nitrogen and perform vacuum freeze drying, and then slice it to obtain bacterial cellulose; S1.3: Add polyethersulfone to dimethyl sulfoxide at a solid-liquid ratio of 1 g:35 mL, stir thoroughly to dissolve, and obtain a polyethersulfone solution; S1.4: adding the bacterial cellulose to the polyethersulfone solution, stirring and mixing, and then adding benzoyl peroxide while stirring to obtain a mixed reaction solution, wherein the molar ratio of polyethersulfone to bacterial cellulose is 1:0.6, and the solid-liquid ratio of benzoyl peroxide to polyethersulfone solution is 1 g:80 mL; S1.5: The mixed reaction solution was transferred to a constant temperature water bath, heated and stirred at 60°C for 2 h, and then kept at this temperature for 8 h to obtain a casting solution; S1.6: Use a scraper to apply the above casting solution on a glass plate, and place it in a vacuum drying oven for vacuum drying for 10-12 hours to obtain a modified base film; S2: Preparation of modified conductive base film Pyrrole was added to deionized water at a volume ratio of 1:140, and the mixture was stirred and mixed evenly. Then, anthraquinone-2-sulfonic acid sodium salt was added, and ultrasonic treatment was performed for 20 minutes to uniformly disperse the mixture to obtain a mixed solution. Then, the modified base film was immersed in the mixed solution, and allowed to stand in an ice water bath at 0°C for 1 hour. Then, ferric chloride was added, and the reaction was allowed to stand for 2 hours. Then, the modified base film after the reaction was taken out, and the modified conductive base film was obtained after washing and drying, wherein the molar ratio of anthraquinone-2-sulfonic acid sodium salt to pyrrole was 1:8, and the molar ratio of ferric chloride to pyrrole was 1.3:1; S3: Preparation of three-dimensional composite electric heating materials S3.1: Add nickel nitrate hexahydrate, cobalt nitrate hexahydrate, aluminum nitrate nonahydrate and urea into deionized water at a solid-liquid ratio of 1g:1.2g:1.1g:120g:100mL, heat and stir at 70°C for 8h, stand for 10h, filter and wash, and calcine at 800°C for 1h to obtain a growth raw material; S3.2: The above growth raw materials are evenly dispersed on the substrate, and then placed in a tube furnace, with methane as the carbon source and argon as the protective gas, the methane flow rate is controlled to be 30 sccm and the argon flow rate is controlled to be 45 sccm, the tube furnace is heated to 800°C at 5°C / min, and after the reaction is kept at this temperature for 20 minutes, the temperature is lowered to 40°C at 5°C / min, and then cooled to room temperature along with the furnace to obtain a composite material; S3.3: placing the composite material in a high-pressure reactor, adding 0.1 mol / L hydrochloric acid aqueous solution until the composite material is completely immersed, stirring and mixing evenly, reacting at 180°C under high pressure for 10 hours, cooling naturally to room temperature, filtering, washing and drying to obtain a three-dimensional composite electric heating material; S4: Surface modified three-dimensional composite electric heating material S4.1: Add the three-dimensional composite electric heating material obtained in step S3.3 to toluene at a solid-liquid ratio of 1 g:35 mL, ultrasonically disperse for 20 min, then add (3-aminopropyl)triethoxysilane, stir and mix thoroughly to obtain a mixed suspension, wherein the volume ratio of (3-aminopropyl)triethoxysilane to toluene is 1:140; S4.2: heating the mixed suspension at 110° C. for 12 h, cooling naturally to room temperature, centrifuging, washing and drying to obtain an amino-functionalized composite material; S4.3: Add the amino-functionalized composite material and pyridine into dichloromethane at a solid-liquid ratio of 1 g: 8 mL: 10 mL, ultrasonically disperse for 20 min, then add succinic anhydride, stir and react for 16 h, centrifuge, wash and dry to obtain a carboxyl-functionalized composite material, wherein the mass ratio of succinic anhydride to the amino-functionalized composite material is 2:1; S4.4: Cholesterol was dissolved in dimethyl sulfoxide at a solid-liquid ratio of 1 g:30 mL, and then the carboxyl functionalized composite material was added at a solid-liquid ratio of 1 g:60 mL, and ultrasonically dispersed for 20 min to obtain a composite suspension; S4.5: adding concentrated sulfuric acid to the composite material suspension at a volume ratio of 1:100, and heating under reduced pressure at 60°C for 8 hours, cooling naturally to room temperature, centrifuging, washing and vacuum drying to obtain a surface-modified three-dimensional composite electric heating material; S5: Preparation of composite electric heating film S5.1: By weight, 5 parts of xylene and 40 parts of 2,4-diphenylmethane diisocyanate were fully stirred and mixed, and then 40 parts of castor oil were added, and heated and stirred at 70°C for 2 hours, and then 1 part of dibenzoyl peroxide and dichloromethane were added, and the stirring was continued for 1 hour, and the polyurethane resin was obtained by decompression and degassing; S5.2: adding epoxy-modified silicone resin, polysiloxane silicone resin, xylene and dibutyltin dilaurate to the polyurethane resin in a mass ratio of 10:0.5:0.5:2:1, stirring and dispersing the mixture evenly to obtain a modified polyurethane adhesive; S5.3: adding the surface-modified three-dimensional composite electric heating material obtained in step S4.5 to the modified polyurethane adhesive solution at a mass ratio of 1.1:1, stirring and mixing evenly, and obtaining the electric heating adhesive solution after vacuum degassing; S5.4: immersing the modified conductive base film obtained in step S2 in the above-mentioned electric heating glue solution, ultrasonically treating for 10 minutes, then taking out and drying and curing to obtain a composite heating film material; S5.5: Prepare electrodes on both sides of the surface of the composite heating film material, respectively, and then package them to obtain a composite electric heating film.

[0021] Example 2 A preparation process of a high-performance composite electric heating film comprises the following steps: S1: Preparation of modified base film S1.1: Activate Gluconacetobacter and inoculate it into a culture medium, and after static culture at 30°C for 7 days, collect the film material produced on the surface of the culture medium, and repeatedly rinse it with deionized water for 4 times to obtain a bacterial cellulose film, wherein the culture medium includes 20 g / L glucose, 10 g / L yeast extract, 5 g / L peptone, 6 g / L disodium hydrogen phosphate dodecahydrate, 1.5 g / L citric acid monohydrate and 0.5 g / L magnesium sulfate heptahydrate; S1.2: soak the bacterial cellulose film in a 0.1 mol / L sodium hydroxide solution, heat it at 95°C for 1.5 h, and then soak it in deionized water for 1.5 h. Take it out, drain it, pour it with liquid nitrogen, and freeze-dry it in vacuum, and then slice it to obtain bacterial cellulose; S1.3: Add polyethersulfone to dimethyl sulfoxide at a solid-liquid ratio of 1 g:40 mL, stir thoroughly to dissolve, and obtain a polyethersulfone solution; S1.4: adding the bacterial cellulose to the polyethersulfone solution, stirring and mixing, and then adding benzoyl peroxide while stirring to obtain a mixed reaction solution, wherein the molar ratio of polyethersulfone to bacterial cellulose is 1:0.7, and the solid-liquid ratio of benzoyl peroxide to polyethersulfone solution is 1 g:90 mL; S1.5: The mixed reaction solution was transferred to a constant temperature water bath, heated and stirred at 70°C for 3 h, and then kept at this temperature for 9 h to obtain a casting solution; S1.6: Use a scraper to apply the above casting solution on a glass plate, and place it in a vacuum drying oven for vacuum drying for 11 hours to obtain a modified base film; S2: Preparation of modified conductive base film Pyrrole was added into deionized water at a volume ratio of 1:145, and the mixture was stirred and mixed evenly. Then, anthraquinone-2-sulfonic acid sodium salt was added, and ultrasonic treatment was performed for 25 minutes to uniformly disperse the mixture to obtain a mixed solution. Then, the modified base film was immersed in the mixed solution, and allowed to stand in an ice water bath at 0°C for 1.5 hours. Then, ferric chloride was added, and the reaction was allowed to stand for 2.5 hours. Then, the modified base film after the reaction was taken out, and the modified conductive base film was obtained after washing and drying, wherein the molar ratio of anthraquinone-2-sulfonic acid sodium salt to pyrrole was 1:9, and the molar ratio of ferric chloride to pyrrole was 1.4:1. S3: Preparation of three-dimensional composite electric heating materials S3.1: Add nickel nitrate hexahydrate, cobalt nitrate hexahydrate, aluminum nitrate nonahydrate and urea to deionized water at a solid-liquid ratio of 1g:1.4g:1.2g:125g:110mL, heat and stir at 75°C for 9h, stand for 11h, filter and wash, and calcine at 850°C for 1.5h to obtain a growth raw material; S3.2: The above growth raw materials are evenly dispersed on the substrate, and then placed in a tube furnace, with methane as the carbon source and argon as the protective gas, the methane flow rate is controlled to be 35 sccm and the argon flow rate is 50 sccm, the tube furnace is heated to 900°C at 5°C / min, and after the reaction is kept at this temperature for 25 minutes, the temperature is lowered to 45°C at 5°C / min, and then cooled to room temperature along with the furnace to obtain a composite material; S3.3: placing the composite material in a high-pressure reactor, adding 0.1 mol / L hydrochloric acid aqueous solution until the composite material is completely immersed, stirring and mixing evenly, reacting at 190° C. under high pressure for 11 hours, cooling naturally to room temperature, filtering, washing and drying to obtain a three-dimensional composite electric heating material; S4: Surface modified three-dimensional composite electric heating material S4.1: Add the three-dimensional composite electric heating material obtained in step S3.3 to toluene at a solid-liquid ratio of 1 g:40 mL, ultrasonically disperse for 25 min, then add (4-aminopropyl)triethoxysilane, stir and mix thoroughly to obtain a mixed suspension, wherein the volume ratio of (3-aminopropyl)triethoxysilane to toluene is 1:145; S4.2: heating the mixed suspension at 115° C. for 14 h, cooling naturally to room temperature, centrifuging, washing and drying to obtain an amino-functionalized composite material; S4.3: Add the amino-functionalized composite material and pyridine into dichloromethane at a solid-liquid ratio of 1 g: 9 mL: 11 mL, ultrasonically disperse for 25 min, then add succinic anhydride, stir and react for 17 h, centrifuge, wash and dry to obtain a carboxyl-functionalized composite material, wherein the mass ratio of succinic anhydride to the amino-functionalized composite material is 2.5:1; S4.4: Cholesterol was dissolved in dimethyl sulfoxide at a solid-liquid ratio of 1 g:35 mL, and then the carboxyl functionalized composite material was added at a solid-liquid ratio of 1 g:65 mL, and ultrasonically dispersed for 25 min to obtain a composite suspension; S4.5: adding concentrated sulfuric acid to the composite material suspension at a volume ratio of 1:105, and heating under reduced pressure at 65°C for 9 hours, cooling naturally to room temperature, centrifuging, washing and vacuum drying to obtain a surface-modified three-dimensional composite electric heating material; S5: Preparation of composite electric heating film S5.1: By weight, 7 parts of xylene and 45 parts of 2,4-diphenylmethane diisocyanate were fully stirred and mixed, and then 45 parts of castor oil were added, and heated and stirred at 75°C for 2.5 hours, and then 1 part of dibenzoyl peroxide and dichloromethane were added, and the stirring was continued for 1.5 hours, and the polyurethane resin was obtained by decompression and degassing; S5.2: adding epoxy-modified silicone resin, polysiloxane silicone resin, xylene and dibutyltin dilaurate to the polyurethane resin in a mass ratio of 11:0.7:0.7:2.5:1, stirring and dispersing the mixture evenly to obtain a modified polyurethane adhesive; S5.3: adding the surface-modified three-dimensional composite electric heating material obtained in step S4.5 to the modified polyurethane adhesive solution at a mass ratio of 1.2:1, stirring and mixing evenly, and obtaining the electric heating adhesive solution after vacuum degassing; S5.4: immersing the modified conductive base film obtained in step S2 in the above-mentioned electric heating glue solution, ultrasonically treating for 15 minutes, then taking out and drying and curing to obtain a composite heating film material; S5.5: Prepare electrodes on both sides of the surface of the composite heating film material, respectively, and then package them to obtain a composite electric heating film.

[0022] Example 3 A preparation process of a high-performance composite electric heating film comprises the following steps: S1: Preparation of modified base film S1.1: Activate Gluconacetobacter and inoculate it into a culture medium, and after static culture at 32°C for 8 days, collect the film material produced on the surface of the culture medium, and repeatedly rinse it with deionized water for 5 times to obtain a bacterial cellulose film, wherein the culture medium includes 20 g / L glucose, 10 g / L yeast extract, 5 g / L peptone, 6 g / L disodium hydrogen phosphate dodecahydrate, 1.5 g / L citric acid monohydrate and 0.5 g / L magnesium sulfate heptahydrate; S1.2: soak the bacterial cellulose film in a 0.1 mol / L sodium hydroxide solution and heat it at 100°C for 2 hours, then soak it in deionized water for 2 hours, take it out and drain it, pour it with liquid nitrogen and perform vacuum freeze drying, and then slice it to obtain bacterial cellulose; S1.3: Add polyethersulfone to dimethyl sulfoxide at a solid-liquid ratio of 1 g:45 mL, stir thoroughly to dissolve, and obtain a polyethersulfone solution; S1.4: adding the bacterial cellulose to the polyethersulfone solution, stirring and mixing, and then adding benzoyl peroxide while stirring to obtain a mixed reaction solution, wherein the molar ratio of polyethersulfone to bacterial cellulose is 1:0.8, and the solid-liquid ratio of benzoyl peroxide to the polyethersulfone solution is 1 g:100 mL; S1.5: The mixed reaction solution was transferred to a constant temperature water bath, heated and stirred at 80°C for 4 hours, and then kept at this temperature for 10 hours to obtain a casting solution; S1.6: Use a scraper to apply the above casting solution on a glass plate, and place it in a vacuum drying oven for vacuum drying for 10-12 hours to obtain a modified base film; S2: Preparation of modified conductive base film Pyrrole was added to deionized water at a volume ratio of 1:150, and the mixture was stirred and mixed evenly. Then, anthraquinone-2-sulfonic acid sodium salt was added, and ultrasonic treatment was performed for 30 minutes to uniformly disperse the mixture to obtain a mixed solution. Then, the modified base film was immersed in the mixed solution, and allowed to stand in an ice water bath at 0°C for 2 hours. Then, ferric chloride was added, and the reaction was allowed to stand for 3 hours. Then, the modified base film after the reaction was taken out, and the modified conductive base film was obtained after washing and drying, wherein the molar ratio of anthraquinone-2-sulfonic acid sodium salt to pyrrole was 1:10, and the molar ratio of ferric chloride to pyrrole was 1.5:1. S3: Preparation of three-dimensional composite electric heating materials S3.1: Add nickel nitrate hexahydrate, cobalt nitrate hexahydrate, aluminum nitrate nonahydrate and urea into deionized water at a solid-liquid ratio of 1g:1.6g:1.3g:130g:120mL, heat and stir at 80°C for 10h, stand for 12h, filter and wash, and calcine at 900°C for 2h to obtain a growth raw material; S3.2: The above growth raw materials are evenly dispersed on the substrate, and then placed in a tube furnace, with methane as the carbon source and argon as the protective gas, the methane flow rate is controlled to be 40 sccm and the argon flow rate is 55 sccm, the tube furnace is heated to 1000°C at 5°C / min, and after the reaction is kept at this temperature for 30 minutes, the temperature is lowered to 50°C at 5°C / min, and then cooled to room temperature along with the furnace to obtain a composite material; S3.3: placing the composite material in a high-pressure reactor, adding 0.1 mol / L hydrochloric acid aqueous solution until the composite material is completely immersed, stirring and mixing evenly, and reacting at 200°C under high pressure for 12 hours. After naturally cooling to room temperature, filtering, washing and drying, a three-dimensional composite electric heating material is obtained; S4: Surface modified three-dimensional composite electric heating material S4.1: Add the three-dimensional composite electric heating material obtained in step S3.3 to toluene at a solid-liquid ratio of 1 g:45 mL, ultrasonically disperse for 30 min, then add (3-aminopropyl)triethoxysilane, stir and mix thoroughly to obtain a mixed suspension, wherein the volume ratio of (3-aminopropyl)triethoxysilane to toluene is 1:150; S4.2: heating the mixed suspension at 120° C. for 16 h, cooling naturally to room temperature, centrifuging, washing and drying to obtain an amino-functionalized composite material; S4.3: Add the amino-functionalized composite material and pyridine into dichloromethane at a solid-liquid ratio of 1 g: 10 mL: 12 mL, ultrasonically disperse for 30 min, then add succinic anhydride, stir and react for 18 h, centrifuge, wash and dry to obtain a carboxyl-functionalized composite material, wherein the mass ratio of succinic anhydride to the amino-functionalized composite material is 3:1; S4.4: Cholesterol was dissolved in dimethyl sulfoxide at a solid-liquid ratio of 1 g:40 mL, and then the carboxyl functionalized composite material was added at a solid-liquid ratio of 1 g:70 mL, and ultrasonically dispersed for 30 min to obtain a composite suspension; S4.5: adding concentrated sulfuric acid to the composite material suspension at a volume ratio of 1:110, and heating under reduced pressure at 70°C for 10 hours, cooling naturally to room temperature, centrifuging, washing and vacuum drying to obtain a surface-modified three-dimensional composite electric heating material; S5: Preparation of composite electric heating film S5.1: By weight, 10 parts of xylene and 50 parts of 2,4-diphenylmethane diisocyanate were fully stirred and mixed, and then 50 parts of castor oil were added, and heated and stirred at 80°C for 3 hours, and then 2 parts of dibenzoyl peroxide and dichloromethane were added, and the stirring was continued for 2 hours, and the polyurethane resin was obtained by decompression and degassing; S5.2: adding epoxy-modified silicone resin, polysiloxane silicone resin, xylene and dibutyltin dilaurate to the polyurethane resin in a mass ratio of 12:1:1:3:1, stirring and dispersing the mixture evenly to obtain a modified polyurethane adhesive; S5.3: adding the surface-modified three-dimensional composite electric heating material obtained in step S4.5 to the modified polyurethane adhesive solution at a mass ratio of 1.3:1, stirring and mixing evenly, and obtaining the electric heating adhesive solution after vacuum degassing; S5.4: immersing the modified conductive base film obtained in step S2 in the above-mentioned electric heating glue solution, ultrasonically treating for 20 minutes, then taking out and drying and curing to obtain a composite heating film material; S5.5: Prepare electrodes on both sides of the surface of the composite heating film material, respectively, and then package them to obtain a composite electric heating film.

[0023] Comparative Example 1 The difference between this comparative example 1 and embodiment 1 is that steps S1.4-S1.5 are removed, and the above-mentioned casting liquid in step S1.6 is directly replaced by an equal amount of polyethersulfone solution prepared in S1.3. Specifically, the polyethersulfone solution prepared in S1.3 is scraped onto a glass plate with a scraper, and placed in a vacuum drying oven for vacuum drying for 10 hours to obtain a polyethersulfone membrane, and then the modified base membrane in step S2 is replaced by a polyethersulfone membrane.

[0024] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that step S3 is removed, and the three-dimensional composite electric heating material in step S4.1 is replaced by an equal amount of carbon nanotubes.

[0025] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that step S3 is removed, and the three-dimensional composite electric heating material in step S4.1 is replaced by an equal amount of carbon fiber.

[0026] Comparative Example 4 The difference between this comparative example 4 and example 1 is that step S3 is removed and the three-dimensional composite electric heating material in step S4.1 is replaced by a mixture of equal amounts of carbon nanotubes and carbon fibers, wherein the amounts of carbon nanotubes and carbon fibers added to the mixture are respectively equal to the contents of carbon nanotubes and carbon fibers in the three-dimensional composite electric heating material.

[0027] Comparative Example 5 The difference between this comparative example 5 and example 1 is that step S4 is removed, and the surface-modified three-dimensional composite electric heating material in step S5.3 is replaced by an equal amount of three-dimensional composite electric heating material.

[0028] Performance Testing Test 1: The thermal stability of the modified base film was tested using a thermogravimetric analyzer. 5-10 mg of the modified base film prepared in Examples 1-3 and Comparative Example 1 was placed in a crucible. Nitrogen was used as the protective gas, the heating range was 30-500°C, and the heating rate was 5°C. The temperature at which the modified base film experienced mass loss was tested. The results are shown in Table 1.

[0029] Test 2: The tensile strength of the modified base films prepared in Examples 1-3 and Comparative Example 1 was tested with reference to GB / T 1447-2005. The results are shown in Table 1.

[0030] Table 1: Comparison of thermal stability and toughness test results of Examples 1-3 and Comparative Example 1

[0031] As can be seen from Table 1, when the polyethersulfone membrane was not modified by bacterial cellulose in Comparative Example 1, its mass loss temperature and tensile strength were 340°C and 78 MPa, respectively, both lower than those in Example 1. It can be seen that by first activating Gluconacetobacter and culturing it in a culture medium to produce a bacterial cellulose membrane, which was purified and dried and then added to a dimethyl sulfoxide solution of polyethersulfone, and then a cross-linking agent benzoyl peroxide was added to cross-link and polymerize the polyethersulfone and the bacterial cellulose to modify the polyethersulfone. Since bacterial cellulose has a high degree of crystallinity and can maintain a stable structure at high temperatures, after the polyethersulfone is modified by bacterial cellulose, the high temperature resistance of the modified base membrane can be effectively improved. In addition, since polyethersulfone and bacterial cellulose are cross-linked and polymerized to form a three-dimensional network structure, the intermolecular interaction is enhanced and the stress transfer is improved, which is beneficial to improve the toughness of polyethersulfone, so that the modified base membrane has good flexibility and is suitable for more usage scenarios.

[0032] Test 3: According to JG / T286-200 "Low-temperature radiant electric heating film" and GB / T "General technical conditions for non-metallic substrate infrared radiation heaters", the electric-thermal efficiency conversion rate and electric-thermal radiation conversion rate of the composite electric heating films prepared in Examples 1-3 and Comparative Examples 2-4 were tested. The results are shown in Table 2.

[0033] Table 2: Comparison of the test results of the electric-to-thermal efficiency conversion rate and the electric-to-thermal radiation conversion rate of Examples 1-3 and Comparative Examples 2-4

[0034] It can be seen from Table 2 that when a single carbon nanotube, a single carbon fiber or a mixture of carbon nanotubes and carbon fibers is used in Comparative Examples 2-4, the electric-to-thermal efficiency conversion rate and the electric-to-thermal radiation conversion rate of the obtained electric heating film are lower than those in Example 1. It can be seen that by first using nickel nitrate hexahydrate, cobalt nitrate hexahydrate, aluminum nitrate nonahydrate and urea to mix and heat to generate a ternary metal hydroxide, and then calcining it at a high temperature to make a growth raw material, and then using methane as a carbon source and the growth raw material as a catalyst, using a chemical vapor deposition method to in-situ generate carbon nanotubes and carbon fibers, and then high-pressure water After the growth raw materials are removed by thermal reaction, a three-dimensional composite electric heating material is obtained in which carbon nanotubes and carbon fibers are combined to form a three-dimensional network structure. By forming a three-dimensional network structure, the carbon nanotubes and carbon fibers can complement each other's advantages at different scales, forming more conductive and thermal conductive paths and reducing energy loss during transmission. Therefore, compared with adding a single carbon nanotube or a single fiber to the electric heating glue, adding a three-dimensional composite electric heating material can effectively improve the conductive and thermal conductive properties of the composite heating film material formed by the electric heating glue, thereby improving the heating efficiency of the composite electric heating film and reducing energy loss.

[0035] Test 4: The temperature sensor array was used to measure the heating uniformity of the surface of the electric heating film prepared in Examples 1-3 and Comparative Example 5. The results are shown in Table 3.

[0036] Table 3: Comparison of surface temperatures of the electric heating films obtained in Examples 1-3 and Comparative Example 5

[0037] As can be seen from Table 3, when the three-dimensional composite electric heating material is not modified in Comparative Example 5, the difference between the highest temperature and the lowest temperature on the surface of the prepared electric heating film is much greater than that in Example 1, that is, the surface heating is uneven and there is local overheating. It can be seen that by first using (3-aminopropyl) triethoxysilane to modify the surface of the three-dimensional composite electric heating material to functionalize its surface amino, and then using succinic anhydride to modify the surface of the three-dimensional composite electric heating material with surface amino functionalization again to functionalize its surface carboxyl, and finally using cholesterol to modify the surface of the three-dimensional composite electric heating material with surface carboxyl functionalization, so that cholesterol is grafted to the surface of the three-dimensional composite electric heating material. Since the hydrophobic part of cholesterol can be better compatible with the organic chain segment of polyurethane, the compatibility of the three-dimensional composite electric heating material and the modified polyurethane glue can be improved, so as to improve its dispersibility in the modified polyurethane glue, and prevent the prepared composite electric heating film from having local overheating problems.

[0038] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A preparation process of a high-performance composite electric heating film, characterized in that: The steps include: S1: Preparation of modified base film The activated Gluconacetobacter was inoculated and cultured to prepare a bacterial cellulose membrane, which was purified and sliced, added into a polyethersulfone solution, and then benzoyl peroxide was added for reaction, and then the modified base membrane was obtained by scraping and vacuum drying. S2: Preparation of modified conductive base film Pyrrole is added to deionized water in a volume ratio of 1: (140-150), stirred and mixed evenly, and then anthraquinone-2-sulfonic acid sodium salt is added, ultrasonic treatment is performed for 20-30 minutes, and uniform dispersion is obtained to obtain a mixed solution, and then the modified base film is immersed in the mixed solution, and allowed to stand in a 0°C ice water bath for 1-2 hours, and then ferric chloride is added, and after standing for reaction for 2-3 hours, the modified base film after the reaction is taken out, and washed and dried to obtain a modified conductive base film; S3: Preparation of three-dimensional composite electric heating materials The growth raw materials are prepared with nickel nitrate hexahydrate, cobalt nitrate hexahydrate, aluminum nitrate nonahydrate and urea as raw materials, and then placed in a tube furnace, and methane and argon are introduced to react, and then immersed in deionized water, and diluted hydrochloric acid is added and high-pressure sealing reaction is carried out to obtain a three-dimensional composite electric heating material; S4: Surface modified three-dimensional composite electric heating material The three-dimensional composite electric heating material is dispersed in toluene, and (3-aminopropyl) triethoxysilane is added to react, then dispersed in dichloromethane together with pyridine, and succinic anhydride is added to react, and finally dispersed in a cholesterol dimethyl sulfoxide solution, and concentrated sulfuric acid is added to react to obtain a surface-modified three-dimensional composite electric heating material; S5: Preparation of composite electric heating film Xylene, 2,4-diphenylmethane diisocyanate, castor oil and dibenzoyl peroxide solution are mixed to prepare polyurethane resin, and then epoxy-modified silicone resin, polysiloxane silicone resin, xylene and dibutyltin dilaurate are added to prepare modified polyurethane adhesive solution, and then the above-mentioned modified three-dimensional composite electric heating material is added to prepare electric heating adhesive solution, and the above-mentioned modified conductive base film is immersed in the electric heating adhesive solution to prepare a composite heating film material, and then electrodes are prepared on the surface of the composite heating film material and packaged to obtain a composite electric heating film.

2. The preparation process of a high-performance composite electric heating film according to claim 1, characterized in that: S1 specifically includes the following steps: S1.1: Activate Gluconacetobacter and inoculate into the culture medium, culture at 28-32°C for 6-8 days, collect the membrane material produced on the surface of the culture medium, and repeatedly rinse with deionized water for 3-5 times to obtain the bacterial cellulose membrane; S1.2: soaking the bacterial cellulose film in a 0.1 mol / L sodium hydroxide solution, and heating it at 90-100°C for 1-2 hours, and then soaking it in deionized water for 1-2 hours, taking it out and draining it, pouring it with liquid nitrogen, and performing vacuum freeze drying, and then slicing it to obtain bacterial cellulose; S1.3: Add polyethersulfone to dimethyl sulfoxide at a solid-liquid ratio of 1 g: (35-45) mL, stir thoroughly to dissolve, and obtain a polyethersulfone solution; S1.4: adding the bacterial cellulose to the polyethersulfone solution, stirring and mixing, and then adding benzoyl peroxide while stirring to obtain a mixed reaction solution; S1.5: Transfer the mixed reaction solution to a constant temperature water bath, heat and stir at 60-80°C for 2-4 hours, and then keep it at this temperature for 8-10 hours to obtain a casting solution; S1.6: Use a scraper to apply the above casting solution on a glass plate, and place it in a vacuum drying oven for vacuum drying for 10-12 hours to obtain a modified base film.

3. The preparation process of a high-performance composite electric heating film according to claim 2, characterized in that: S3 specifically includes the following steps: S3.1: Add nickel nitrate hexahydrate, cobalt nitrate hexahydrate, aluminum nitrate nonahydrate and urea into deionized water at a solid-liquid ratio of 1 g: (1.2-1.6) g: (1.1-1.3) g: (120-130) g: (100-120) mL, heat and stir at 70-80 ° C for 8-10 h, and stand for 10-12 h, then filter and wash, and then calcine at 800-900 ° C for 1-2 h to obtain a growth raw material; S3.2: The above growth raw materials are evenly dispersed on the substrate, and then placed in a tube furnace, with methane as the carbon source and argon as the protective gas, the methane flow rate is controlled to be 30-40sccm, and the argon flow rate is controlled to be 45-55sccm, the tube furnace is heated to 800-1000°C at 5°C / min, and after the reaction is kept at this temperature for 20-30min, the temperature is lowered to 40-50°C at 5°C / min, and then cooled to room temperature along with the furnace to obtain a composite material; S3.3: Place the above composite material in a high-pressure reactor, add 0.1 mol / L hydrochloric acid aqueous solution until the composite material is completely immersed, stir and mix evenly, and react at 180-200°C under high pressure and sealed for 10-12 hours. After naturally cooling to room temperature, filter, wash and dry to obtain a three-dimensional composite electric heating material.

4. The preparation process of a high-performance composite electric heating film according to claim 3, characterized in that: S4 specifically includes the following steps: S4.1: Add the three-dimensional composite electric heating material prepared in step S3.3 to toluene at a solid-liquid ratio of 1 g: (35-45) mL, ultrasonically disperse for 20-30 min, then add (3-aminopropyl) triethoxysilane, stir and mix thoroughly to obtain a mixed suspension; S4.2: heating the mixed suspension at 110-120° C. for reflux reaction for 12-16 hours, cooling naturally to room temperature, centrifuging, washing and drying to obtain an amino-functionalized composite material; S4.3: Add the amino-functionalized composite material and pyridine into dichloromethane at a solid-liquid ratio of 1 g: (8-10) mL: (10-12) mL, ultrasonically disperse for 20-30 min, then add succinic anhydride, stir and react for 16-18 h, centrifuge, wash and dry to obtain a carboxyl-functionalized composite material; S4.4: Cholesterol is dissolved in dimethyl sulfoxide at a solid-liquid ratio of 1 g: (30-40) mL, and then the carboxyl functionalized composite material is added at a solid-liquid ratio of 1 g: (60-70) mL, and ultrasonically dispersed for 20-30 min to obtain a composite suspension; S4.5: Add concentrated sulfuric acid to the composite material suspension in a volume ratio of 1: (100-110), and heat under reduced pressure at 60-70°C for 8-10 hours. After naturally cooling to room temperature, centrifuge, wash and vacuum dry to obtain a surface-modified three-dimensional composite electric heating material.

5. The preparation process of a high-performance composite electric heating film according to claim 4, characterized in that: S5 specifically includes the following steps: S5.1: By weight, 5-10 parts of xylene and 40-50 parts of 2,4-diphenylmethane diisocyanate are thoroughly stirred and mixed, and then 40-50 parts of castor oil are added, and heated and stirred at 70-80° C. for 2-3 hours, and then 1-2 parts of dibenzoyl peroxide and dichloromethane are added, and stirring is continued for 1-2 hours, and degassing is carried out under reduced pressure to obtain a polyurethane resin; S5.2: Add epoxy-modified silicone resin, polysiloxane silicone resin, xylene and dibutyltin dilaurate to the above polyurethane resin in a mass ratio of (10-12): (0.5-1): (0.5-1): (2-3): 1, stir and disperse evenly to obtain a modified polyurethane glue solution; S5.3: adding the surface-modified three-dimensional composite electric heating material obtained in step S4.5 to the modified polyurethane adhesive solution according to a mass ratio (1.1-1.3): 1, stirring and mixing evenly, and obtaining the electric heating adhesive solution after vacuum degassing; S5.4: Immerse the modified conductive base film obtained in step S2 in the above-mentioned electric heating glue solution, ultrasonically treat for 10-20 minutes, then take out and dry and solidify to obtain a composite heating film material; S5.5: Prepare electrodes on both sides of the surface of the composite heating film material, respectively, and then package them to obtain a composite electric heating film.

6. The preparation process of a high-performance composite electric heating film according to claim 2, characterized in that: The culture medium included 20 g / L glucose, 10 g / L yeast extract, 5 g / L peptone, 6 g / L disodium hydrogen phosphate dodecahydrate, 1.5 g / L citric acid monohydrate, and 0.5 g / L magnesium sulfate heptahydrate.

7. The preparation process of a high-performance composite electric heating film according to claim 2, characterized in that: The molar ratio of polyethersulfone to bacterial cellulose is 1:(0.6-0.8), and the solid-liquid ratio of benzoyl peroxide to polyethersulfone solution is 1g:(80-100)mL.

8. The preparation process of a high-performance composite electric heating film according to claim 1, characterized in that: The molar ratio of anthraquinone-2-sulfonic acid sodium salt to pyrrole is 1:(8-10), and the molar ratio of ferric chloride to pyrrole is (1.3-1.5):

1.

9. The preparation process of a high-performance composite electric heating film according to claim 4, characterized in that: The volume ratio of (3-aminopropyl)triethoxysilane to toluene is 1:(140-150), and the mass ratio of succinic anhydride to the amino-functionalized composite material is (2-3):

1.

10. A high-performance composite electric heating film, characterized in that: It is prepared by the preparation process of a high-performance composite electric heating film as described in any one of claims 1-9.